An Analysis of Fillers Used in English Speech of Emma Watson & Malala: Amazing Interview - Luthfia, Shabrina Rifda; Nugraheni, Pramita Lutfi; Sekartadji, Larasati (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2024)
This research discuss the fillers used in English speech. This research aims to describe the type of fillers used in English Speech of Emma Watson and Malala: Amazing Interview.  Filler is any words or speech sound that enters the speaker's main point. Filler words are used when the speaker speaks loudly.The data of this research were taken from a video on Youtube with the title Emma Watson and Malala: Amazing Interview. The data collection technique used in this research is through the documentation method, namely by using notes. The form of this research used in this case is a qualitative research method. The reason to choose this video as the data source is that this video has filler as the target of this research related to the problem. This research target is fillers: umm, and, like, well, and so on. The result showed that Emma Watson and Malala used 12 fillers during their conversation. The fillers are umm, okay, actually, so, and, and then, like, well, then, right, ahh, and you know. The "umm" filler was the most frequently used, appearing 68 times, while the "right" and "actually" filler was the least often utilized, occurring only once for each.